Reading Activities in Kauman Area, Parakan, Indonesia, During the Colonial Era Using Mapping Analysis - Purwantiasning, Ari Widyati; Kurniawan, Kemas Ridwan; Suniarti, Pudentia Maria Purenti Sri (International Journal of Geography and Geology, 2019)
This paper aims to identify the activities of a local organization known as Barisan Bambu Runcing as a part of the undertakings of Indonesian warriors in the colonial era, particularly in Kauman, Parakan, Temanggung, Central Java, Indonesia. The role of Indonesian warriors was very particular, as it involved their preparation to fight the Dutch and the Japanese. By identifying such activities in the colonial era, future generations will understand historical events, so they will appreciate history. We have chosen a heritage city in Indonesia as a case study to achieve the research objectives, one known as a city of Bambu Runcing (sharpened bamboo for a traditional weapon), namely Parakan, which is located in Central Java, Indonesia. Parakan, which has been designated as a heritage city since 2015, has a unique character. Its historical area is separated into two sectors: Kauman Area and Pecinan Area. This research employed Kauman Area for the case study because it has a long significant history as the place where Bambu Runcing was established. A qualitative method was used, specifically a historical method through the oral tradition approach, in order to reveal the activities of a moslem Indonesian warriors’ organization which known as Barisan Bambu Runcing in the colonial era, particularly in Kauman Area.